## FANDOM

15 Pages

The Slutsky Equation decomposes the a price change into an income effect and a substitution effect:

${\partial x_i(\mathbf{p}, m) \over \partial p_j} = {\partial h_i(\mathbf{p}, u) \over \partial p_j} - {\partial x_i(\mathbf{p}, m) \over \partial m } x_j(\mathbf{p}, m),\,$


## Derivation Edit

Basic idea: Express Hicksian demand as Marshallian demand using expenditure function and then differentiate.

$h_{i}(p,u)= h_{i}(p,V(p,m)) = x_{i}(p,m) = x_{i}(p, e(p,u)) \,$


2) Differentiate with respect to $p_{j} \,$

$\partial h_{i}(p_{i},u)/\partial p_{j} = \partial x_{i}(p, m)/\partial p_{j}+\partial x_{i}(p, m)/ \partial m \cdot \partial e(p,u)/ \partial p_{j}$


3) Note that by Shephard's Lemma, we can rewrite this as:

$\partial h_{i}(p_{i},u)/\partial p_{j} = \partial x_{i}(p,m)/\partial p_{j}+\partial x_{i}/ \partial m \cdot h_{j}(p,u)$


4) Since $h_{j}(p,V(p,m)) \equiv x_{j}(p,m) \,$, we get:

$\partial h_{i}(p_{i},u)/\partial p_{j} = \partial x_{i}(p,m)/\partial p_{j}+\partial x_{i}(p,m)/ \partial m \cdot x_{j}(p,m)$


5) After rearranging:

$\partial x_{i}(p,m)/\partial p_{j} = \partial h_{i}(p_{i},u)/\partial p_{j} -\partial x_{i}/ \partial m \cdot x_{j}(p,m)$

Community content is available under CC-BY-SA unless otherwise noted.